2009
DOI: 10.1063/1.3257625
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of O17 NMR to p-d hybridization in transition metal perovskites: First principles calculations of large anisotropic chemical shielding

Abstract: A first principles embedded cluster approach is used to calculate O chemical shielding tensors, σ, in prototypical transition metal oxide ABO3 perovskite crystals. Our principal findings are 1) a large anisotropy ofσ between deshielded σx ≃ σy and shielded σz components (z along the Ti-O bond); 2) a nearly linear variation, across all the systems studied, of the isotropic σiso and uniaxial σax components, as a function of the B-O-B bond asymmetry. We show that the anisotropy and linear variation arise from lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…In the literature there have been several attempts to correlate features in NMR spectra with local structural details such as coordination numbers 22 , local atomic bondlength and angular distortion 57 , shortest bondlength 58 , Mulliken charge population 22 etc.…”
Section: Correlation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature there have been several attempts to correlate features in NMR spectra with local structural details such as coordination numbers 22 , local atomic bondlength and angular distortion 57 , shortest bondlength 58 , Mulliken charge population 22 etc.…”
Section: Correlation Analysismentioning
confidence: 99%
“…However, the internal distribution within a given coordination number does not correlate with local geometric descriptors such as local bondlength, angular distortions 57 , or shortest bondlength 58 . To explain this we performed a simple test in the non-spinel model B for γ-alumina by displacing an oxygen atom while keeping the rest fixed and we observed that the NMR parameters were affected in a region extending up to the third coordination shell, thus demonstrating the sensitivity of NMR to non-local structural details.…”
Section: Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…426 A first principles embedded cluster approach is used to calculate O chemical shielding tensors, s, in prototypical transition metal oxide ABO3 perovskite crystals. 427 The DFT B3LYP/SBKJC method is used to calculate the gas-phase optimised geometries of the glycolate oxoperoxo vanadium(V) complexes [V 2 O 2 (OO) 2 (gly) 2 ] 2À , [V 2 O 3 (OO)(gly) 2 ] 2À and [VO(OO)(gly)(H 2 O)] À . The 51 V, 17 O, 13 C and 1 H chemical shifts were calculated for the theoretical geometries in all-electron DFT calculations at the UDFT-IGLO-PW91 level and were subsequently compared with the experimental chemical shifts in solution.…”
Section: 16mentioning
confidence: 99%
“…Another good example of embedded cluster approach is the study of the17 O shielding dependence on structural parameters, B-O bond length and B-O-B angle, in ABO 3 transition metal perovskite crystals 166. The authors use a cluster embedded in point charges to model the long range Coulomb interactions in the ABO 3 materials.…”
mentioning
confidence: 99%